ChemInform Abstract: Catalytic Strategies Toward Selective Hydrogenation of Aromatic Ketones and Phenols: Facile Synthesis of Cyclohexyl Ketones. Issue 20 (April 2016) - Wei, Yu; Zeng, Xiaoming
Abstract: Review: [24 refs.